Raising the bar (8). Issue 3 (3rd July 2018) - Elhorst, Paul; Abreu, Maria; Amaral, Pedro; Bhattacharjee, Arnab; Corrado, Luisa; Doran, Justin; Fingleton, Bernard; Fuerst, Franz; Garretsen, Harry; Igliori, Danilo; Gallo, Julie Le; McCann, Philip; et al.
ABSTRACT: This editorial summarizes the papers published in issue 13 (3) so as to raise the bar in applied spatial economic research and highlight new trends. The first paper challenges the home market hypothesis that large countries host more firms relative to their size than small countries by considering the lobbying activities of multinational firms. The second paper analyzes the implications of a spatial weight matrix used to estimate a spatial econometric model that depends on an endogenous economic variable. By adding a spatial context, the third paper provides a novel contribution to the literature on international norms in de facto measures of human rights performance. The fourth paper examines the determinants of accepting informal work in Poland. The fifth paper deals with non-stationarity and cointegration in a dynamic spatial econometric panel data model when the number of observations in the time – rather than in the cross-sectional– domain tends to infinity.